2014
DOI: 10.1517/14656566.2014.897695
|View full text |Cite
|
Sign up to set email alerts
|

Nintedanib for the treatment of non-small-cell lung cancer

Abstract: Recent Phase III trials have shown promising efficacy results of nintedanib in NSCLC; however, many questions still need to be answered before it is put into routine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
(23 reference statements)
0
5
0
1
Order By: Relevance
“…However, more recent clinical trials investigating VEGFR-2-targeted therapy demonstrated a relatively positive performance, without induction of hemoptysis, in patients exhibiting NSCLC containing squamous cell carcinoma ( 24 ). In addition, small molecule inhibitors of receptor tyrosine kinases, which work with VEGFR-2, nintedanib, sunitinib, sorafenib, vandetanib and vatalanib, have been tested as potential anticancer therapies ( 25 , 26 ). Due to the association between myoferlin and VEGFR-2 observed in the current study, the efficacy of myoferlin as a therapeutic agent may require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent clinical trials investigating VEGFR-2-targeted therapy demonstrated a relatively positive performance, without induction of hemoptysis, in patients exhibiting NSCLC containing squamous cell carcinoma ( 24 ). In addition, small molecule inhibitors of receptor tyrosine kinases, which work with VEGFR-2, nintedanib, sunitinib, sorafenib, vandetanib and vatalanib, have been tested as potential anticancer therapies ( 25 , 26 ). Due to the association between myoferlin and VEGFR-2 observed in the current study, the efficacy of myoferlin as a therapeutic agent may require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking the PDGFR signaling by either specific neutralizing antibodies that target the receptors or RTK inhibitors that disrupt the kinase activity has proven to have clinical efficacy in treating a number of human malignancies, including NSCLC. 35 38 Criteria for selecting candidate RTK inhibitors in cancer therapy include minimal toxicity and higher affinity with mutated forms of the kinase targets that are frequently present in cancer patients. Crenolanib, a potent RTK inhibitor with narrow and selective reactivity against both wild-type and mutated FLT3 and PDGFR (including PDGFRα and PDGFRβ), represents the first anticancer RTK inhibitor with predictably minimal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Adenovirus-mediated overexpression of VEGF had no effect on aortic atherosclerotic plaque deposition or neovascularization [189], but systemic therapy with VEGF inhibitor led to accelerated atherogenesis [190]. Newer oncologic antiangiogenesis agents targeting combinations of the FGF, PDGF, and/or VEGF receptors have not demonstrated similar toxicities but evaluation in the treatment of peripheral arterial disease has not been pursued [191,192,193]. The long-term therapy required for a chronic disease such as peripheral artery disease may be another limiting factor in the utilization of these pharmaceuticals; therefore, research pursuing the more specific alternative of a selective MMP inhibitor to mitigate plaque neovascularization may be a more productive avenue.…”
Section: Targets To Promote Plaque Stabilizationmentioning
confidence: 99%